Temporal correlations among demographic parameters are ubiquitous but highly variable across species - Rémi Fay; Sandra Hamel; Martijn van de Pol; Jean‐Michel Gaillard; Nigel G. Yoccoz; Paul Acker; Matthieu Authier; Benjamin Larue; Christie Le Coeur; Kaitlin R. Macdonald; Alex Nicol‐Harper; Christophe Barbraud; et al. (Ecology Letters, 2022)
Temporal correlations among demographic parameters can strongly influence population dynamics. Our empirical knowledge, however, is very limited regarding the direction and the magnitude of these correlations and how they vary among demographic parameters and species’ life histories. Here, we use long‐term demographic data from 15 bird and mammal species with contrasting pace of life to quantify correlation patterns among five key demographic parameters: juvenile and adult survival, reproductive probability, reproductive success and productivity. Correlations among demographic parameters were ubiquitous, more frequently positive than negative, but strongly differed across species. Correlations did not markedly change along the slow‐fast continuum of life histories, suggesting that they were more strongly driven by ecological than evolutionary factors. As positive temporal demographic correlations decrease the mean of the long‐run population growth rate, the common practice of ignoring temporal correlations in population models could lead to the underestimation of extinction risks in most species.

Natal experience and pre‐breeding environmental conditions affect lay date plasticity in Savannah Sparrows - Joseph B. Burant; Eric W. Heisey; Nathaniel T. Wheelwright; Amy E. M. Newman; Shannon Whelan; Daniel J. Mennill; Stéphanie M. Doucet; Greg W. Mitchell; Bradley K. Woodworth; D. Ryan Norris (Ecology, 2022)
Phenotypic plasticity allows organisms to adjust the timing of life‐history events in response to environmental and demographic conditions. Shifts by individuals in the timing of breeding with respect to variation in age and temperature are well documented in nature, and these changes are known to scale to affect population dynamics. However, relatively little is known about how organisms alter phenology in response to other demographic and environmental factors. We investigated how pre‐breeding temperature, breeding population density, age, and rainfall in the first month of life influenced the timing and plasticity of lay date in a population of Savannah Sparrows ( Passerculus sandwichensis ) monitored over 33 yr (1987–2019). Females that experienced warmer pre‐breeding temperatures tended to lay eggs earlier, as did older females, but breeding population density had no effect on lay date. Natal precipitation interacted with age to influence lay date plasticity, with females that experienced high precipitation levels as nestlings advancing lay dates more strongly over the course of their lives. We also found evidence for varied pace of life; females that experienced high natal precipitation had shorter lifespans and reduced fecundity, but more nesting attempts over their lifetimes. Rainfall during the nestling period increased through time, while population density and fecundity declined, suggesting that increased precipitation on the breeding grounds may be detrimental to breeding females and ultimately the viability of the population as a whole. Our results suggest that females adjust their laying date in response to pre‐breeding temperature, and as they age, while presenting new evidence that environmental conditions during the natal period can affect phenological plasticity and generate downstream, population‐level effects.

The buzz segment of Savannah sparrow song is a population marker - Heather Williams; Clint W. Robins; D. Ryan Norris; Amy E. M. Newman; Corey R. Freeman-Gallant; Nathaniel T. Wheelwright; Daniel J. Mennill (Journal of Ornithology, 2019)

Local density regulates migratory songbird reproductive success through effects on double‐brooding and nest predation - Bradley K. Woodworth; Nathaniel T. Wheelwright; Amy E. M. Newman; D. Ryan Norris (Ecology, 2017)
Knowledge of the density‐dependent processes that regulate animal populations is key to understanding, predicting, and conserving populations. In migratory birds, density‐dependence is most often studied during the breeding season, yet we still lack a robust understanding of the reproductive traits through which density influences individual reproductive success. We used 27‐yr of detailed, individual‐level productivity data from an island‐breeding population of Savannah sparrows Passerculus sandwichensis to evaluate effects of local and total annual population density on female reproductive success. Local density (number of neighbors within 50 m of a female's nest) had stronger effects on the number of young fledged than did total annual population density. Females nesting in areas of high local density were more likely to suffer nest predation and less likely to initiate and fledge a second clutch, which led to fewer young fledged in a season. Fledging fewer young subsequently decreased the likelihood of a female recruiting offspring into the breeding population in a subsequent year. Collectively, these results provide insight into the scale and reproductive mechanisms mediating density‐dependent reproductive success and fitness in songbirds.

Differential migration and the link between winter latitude, timing of migration, and breeding in a songbird - Bradley K. Woodworth; Amy E. M. Newman; Sheela P. Turbek; Bryant C. Dossman; Keith A. Hobson; Leonard I. Wassenaar; Greg W. Mitchell; Nathaniel T. Wheelwright; D. Ryan Norris (Oecologia, 2016)

Social pairing and female mating fidelity predicted by restriction fragment length polymorphism similarity at the major histocompatibility complex in a songbird - Corey R. Freeman‐Gallant; Michael Meguerdichian; Nathaniel T. Wheelwright; Suzanne V. Sollecito (Molecular Ecology, 2003)
Female birds often copulate outside the pair‐bond to produce broods of mixed paternity, but despite much recent attention the adaptive significance of this behaviour remains elusive. Although several studies support the idea that extra‐pair copulations (EPCs) allow females to obtain ‘good genes’ for their offspring, many others have found no relationship between female mating fidelity and traits likely to reflect male quality. A corollary to the good genes hypothesis proposes that females do use EPCs to increase the quality of young, but it is the interaction between maternal and paternal genomes — and not male quality per se — that is the target of female choice. We tested this ‘genetic compatibility’ hypothesis in a free‐living population of Savannah sparrows ( Passerculus sandwichensis ) by determining whether females mated nonrandomly with respect to the major histocompatibility complex ( Mhc ). During both the 1994 and 1995 breeding seasons, female yearlings (but not older birds) avoided pairing with Mhc ‐similar males ( P Mhc similarity between mates also predicted the occurrence of extra‐pair young in first broods ( P P = 0.007). The overall genetic similarity between adults tended to predict female mating fidelity, but with less precision than their Mhc similarity ( P = 0.09). In contrast, females appeared insensitive to the size, weight or age of males, none of which explained variation in female mating fidelity. Taken together, these results are consistent with the hypothesis that females sought complementary genes for their offspring and suggest either that the benefits of heterozygosity (at the Mhc ) drive female mating patterns or that the avoidance of inbreeding is an ultimate cause of social and genetic mate choice in Savannah sparrows.

State‐of‐the‐Art Conservation Literature - Nathaniel T. Wheelwright (Conservation Biology, 2003)